2008
DOI: 10.1021/ie800434e
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Removal from Municipal Landfill Leachate by Clinoptilolite Bed Columns: Breakthrough Modeling and Error Analysis

Abstract: In this study, a clinoptilolite bed column system was used to remove ammonium from municipal landfill leachate. Laboratory-scale column experiments were conducted in upflow fixed-bed and fluidized-bed modes with different ammonium concentrations. Ammonium removal was managed mainly by Ca2+ and K+ cations of clinoptilolite, and higher treatment performances were obtained at lower flow rates. On the other hand, higher effluent volumes and removal rates were produced by lower ammonium concentrations, and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Various treatment technologies have been applied to remove ammonium from leachate, such as biological processes, [5,6] electro-oxidation, [7,8] air stripping, [3,4] chemical precipitation, [9,10] adsorption and ion exchange. [1,11] Among these treatment methods, ion exchange using zeolites is very attractive due to its low cost and relatively simple application. [1,11] More than 50 species of natural zeolites have been recognized in the world.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various treatment technologies have been applied to remove ammonium from leachate, such as biological processes, [5,6] electro-oxidation, [7,8] air stripping, [3,4] chemical precipitation, [9,10] adsorption and ion exchange. [1,11] Among these treatment methods, ion exchange using zeolites is very attractive due to its low cost and relatively simple application. [1,11] More than 50 species of natural zeolites have been recognized in the world.…”
Section: Introductionmentioning
confidence: 99%
“…[1,11] Among these treatment methods, ion exchange using zeolites is very attractive due to its low cost and relatively simple application. [1,11] More than 50 species of natural zeolites have been recognized in the world. [12] Zeolites contain exchangeable cations, such as K + , Ca 2+ and Mg 2+ , in its structural framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia and ammonium ions are the more commonly encountered N compounds in waste water and groundwater. There are different methods for removing ammonium ions from wastewaters: air stripping, chemical treatment, selective ion exchange, adsorption and biological nitrification-denitrification [1][2][3][4][5][6][7]. Previously we reported that carbon obtained from Bulgarian lignite from Chukurovo deposit by one-step steam pyrolysis-activation followed by oxidative modification gave comparable results despite its worse texture parameters as compared with Norit GAC 1240 oxidized in an analogous way and was a more promising adsorbent as a means of ammonia removal from aqueous solutions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The various aspects of removal from aqueous solutions by clinoptilolite have been investigated by many researchers [6,7,[9][10][11][12][13][14][15]. It is reported to have a classical alumina silicate age-like structure.…”
Section: Introductionmentioning
confidence: 99%